Kajian Aspek Reproduksi Ikan Lais Ompok hypophthalmus di Sungai Kampar, Kecamatan Langgam, Kabupaten Pelalawan, Provinsi Riau - Elvyra, Roza; Solihin, Dedy Duryadi; Affandi, Ridwan; Junior, Zairin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
Lais fish of Ompok hypophthalmus is one of high economic fish in Kampar river. It should be protected fromdecreasing of it population estimated due to decreasing of habitat quality and increasing of exploitation. Theobjectives of the research are to study reproduction biology of lais fish as the basic data for conservation. Thisresearch was conducted from January 2007 to January 2008. The results of O. hypophthalmus reproductionaspect show that the smallest female of maturity is 22,9 cm and male is 22,6 cm; the spawning season onSeptember to November; O. hypophthalmus is more appropriate spawning location to oxbow lake that closerelation with tributary; the spawning pattern indicated total spawner fish; the fecundity ranges from 3111 to 11164eggs and the egg diameter ranges 0,41-1,13 mm.